The Level Of Dependence Of Sidoarjo Communities On Social Media Post Pandemi Covid-19: Tingkat Ketergantungan Masyarakat Sidoarjo terhadap Media Sosial Pasca Pandemi COVID-19 - Mahendra, Alvino Achlan; Aesthetika, Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative study employs virtual ethnography to investigate the motives underlying the use of social media among individuals in Sidoarjo Regency, a rapidly developing region in Indonesia. With the advent of modern technology and the influence of the COVID-19 pandemic, social media has become crucial for disseminating information and providing entertainment to society. The research involved five informants and primarily focused on WhatsApp as a substitute communication tool facilitating their daily activities. The study explores the goals, methods, results, and implications of social media usage in Sidoarjo, highlighting its significance in supporting regional economic development. The findings shed light on the wide reach, convenience, and cost-effectiveness of social media as a mass communication medium. This research contributes to the broader understanding of the role of social media in contemporary society and its implications for communication practices and socio-economic dynamics. Highlights: The study examines the motives underlying social media usage in Sidoarjo Regency, Indonesia, through virtual ethnography. The research focuses on WhatsApp as a substitute communication tool and its impact on daily activities of individuals in Sidoarjo. The findings highlight the significance of social media in supporting regional economic development, emphasizing its wide reach and cost-effectiveness. Keywords: Social media usage, Virtual ethnography, Motives, Sidoarjo Regency, Economic development.